Seed treatment and foliar fungicide application to control soybean rust - Godoy, Cláudia Vieira; Henning, Ademir Assis (Pesquisa Agropecuaria Brasileira, 2008)
The objective of this work was to evaluate the effect of soybean seed treatment with fluquinconazole and foliar fungicide application on soybean rust management, in three sowing dates, during the 2007/2008 growing season, in Londrina, PR, Brazil. The experimental design was a randomized complete block, with a factorial arrangement of 2x5 (with two treatments of seeds with fluquinconazole, and five foliar fungicide applications) in the first sowing time, and of 2x6 in the second and third sowing time. The parameters evaluated were: the area under disease progress curve, the normalized difference vegetation index (NDVI) and yield. There was no significant interaction between seed treatment with fluquinconazole and fungicide mixture in foliar applications. Seed treatment with fluquinconazole did not delay the disease progress, and showed no significant difference from treatment without fluquinconazole for sowing time or any other parameter evaluated. The NDVI showed high correlation with disease severity and yield, in all sowing times. Yield response for time and the interval of application varied according to sowing dates and the time of disease onset.